An Efficient Smart Flood Detection and Alert System based on Automatic Water Level Recorder Approach using IoT - Mansi Joshi; S. Murali (International Journal of Computational and Experimental Science and Engineering, 2025)
An innovative flood detection system may track an increase in water levels. Deployed in cities or other areas of interest, the system consists of sensors. Both mains energy and solar power are viable options for the sensors. To detect impending flooding promptly, a flood warning system uses reliable and up-to-date sensing equipment such as rain gauges, water level sensors, and flow rate sensors for the smart alert system. The challenging characteristics of smart flood detection and alert systems are that some people may not be able to access the warnings, and flash floods may happen too quickly for a warning to be adequate. Hence, in the proposed method, the Automatic Water Level Recorder enabled the Internet of Things (AWLR-IoT), which integrates a low-cost cloud to overcome the challenges of the smart flood detection and alert system and increase optimization modelling and efficiency. Among the most destructive natural catastrophes that may happen on Earth is flooding. After that, a Wireless Sensor Network (WSN) is used to accomplish the flood prediction utilizing data from sensors enabled by the Internet of Things. Heavy rainfall and the following water outflow cause flooding in nations with certain climate conditions. The system monitors humidity, temperature, water level, water rise rate, and rainfall to identify when a flood is imminent. The function of the AWLR-IoT sensor is for monitoring and recording in a database with real-time sensing. This research shows that the low-cost AWLR-IoT sensor has reduced processing time compared to conventional data processing.